DAMPAK ASESMEN FORMATIF BERBASIS GAMIFIKASI QUIZIZZ DAN TTS TERHADAP HASIL BELAJAR SISWA - Asdar, Fajriani; Husnul Khatimah; H, Nurhikmah; Ishak, Suryadi; Safaruddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study investigates the impact of gamification-based formative assessment, specifically using Quizizz and Crossword Puzzles (TTS), on student learning outcomes in economics, focusing on the material concerning the division and scope of economics. While previous research confirmed the benefits of game-based assessments in enhancing motivation and learning, a direct comparative study between Quizizz and TTS was rare, especially on this fundamental economic topic. Employing a quantitative approach with a Quasi-Experimental Design, the study used Purposive Sampling to select two groups of 36 students each at UPT SMAN 13 Sinjai: one group treated with Quizizz and the other with TTSData analysis using JASP involved the Independent Samples t-test on post-test score. The descriptive analysis showed that the TTS group achieved a significantly higher average score (x=82.92) compared to the Quizizz group (x =72.11). The Independent Samples t-test confirmed a statistically significant difference (p < 0.001) in learning outcomes, leading to the rejection of the null hypothesis. The conclusion highlights that the Crossword Puzzle (TTS) method is substantially more effective due to its ability to encourage deeper cognitive processing, active elaborative encoding, and a more stress-free, engaging learning environment, leading to stronger long-term memory retention than the quick-response nature of Quizizz